2023
DOI: 10.1063/5.0136417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radial clearance on the dynamic behavior of adjustable journal bearings in turbulent and laminar flow regimes

Abstract: Radial clearance critically affects journal bearing performance, specifically the lubrication performance. This study investigates the lubrication characteristics of a journal bearing with adjustable radial clearance and compares the dynamic behavior of the bearing under laminar and turbulent flow regimes. The adjustable bearing exhibits two states of oil film pressure at different radial clearances. When the radial clearance is reduced from 100% cr to 80% cr, the oil film pressure is present only on the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Moreover, the lubrication performances of bearings with groove angles of 36 • and 18 • in a turbulent regime were analyzed, and the load capacity improved as the misalignment angle increased [22]. Further studies have shown that local turbulence has a significant impact on the friction coefficient [23,24], and the influence of micro-groove on lubrication characteristics and bearing capacity varies with variations of the eccentricity ratio [25,26]. The effect of the micro-groove on the lubrication performance of water-lubricated bearings during start-up was also studied [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lubrication performances of bearings with groove angles of 36 • and 18 • in a turbulent regime were analyzed, and the load capacity improved as the misalignment angle increased [22]. Further studies have shown that local turbulence has a significant impact on the friction coefficient [23,24], and the influence of micro-groove on lubrication characteristics and bearing capacity varies with variations of the eccentricity ratio [25,26]. The effect of the micro-groove on the lubrication performance of water-lubricated bearings during start-up was also studied [27][28][29].…”
Section: Introductionmentioning
confidence: 99%